Understanding the crystallization behavior of α-lactose monohydrate (α-LM) through molecular interaction in selected solvents and solvent mixtures under different growth conditions. Issue 13 (9th March 2016) - Parimaladevi, P.; Srinivasan, K.
Abstract : From this study, it was found that the solute–solvent interactions play a major role in the nucleation of α-LM from DMSO–water solvent mixtures. A novel method for the growth of bulk single crystals of α-LM from pure DMSO and water was identified. Abstract : Crystallization behavior of α-lactose monohydrate (α-LM) single crystals from selected solvents and solvent mixtures was studied. Upon crystallizing α-LM from pure dimethylsulfoxide (DMSO) at 32 °C, a colloidal creamy suspension was detected and the reason behind this result was analyzed. Nucleation of α-LM in DMSO involves a longer time interval and the nucleation rate is very low. To overcome these difficulties, different mole fractions of polar protic solvents such as water and ethanol were added to the polar aprotic solvent, DMSO. In these solvent mixtures, various levels of DMSO–water clusters existed and their influence on the nucleation and growth of α-LM was also investigated. Based on the results obtained, we developed a new approach for the crystallization of α-LM with uniform crystal size distribution from pure DMSO at 32 °C. A good optically transparent single crystal of α-LM was grown from water and was found to possess a larger size among the ones reported so far.